Numerical Analysis of an Aircraft Wing - et. al., S. Solomon Raj, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
A wing is a structural component of aircraft which is used to produce lift during the flight. Wing structure contains skin, ribs and spars sections. Wings are the most prominent lift producing component of the aircraft. The selection and design of the profile do depend on the type of the aircraft and its purpose. Testing the wing structures experimentally is very expensive and time consuming. In the present study a standard NACA profile considered is modeled in SOLID WORKS and structural analysis is carried out using ANSYS workbench. The stress analysis is carried out to examine the stresses along the length of the wing. Wing with and without spar and ribs are taken for analysis. Aluminum 2024-T3, steel and balsa wood are considered for the study. The purpose of the present study is to correlate and validate the finite element model against the modal test for further complex analysis. The deformation pattern and the associated stress fields are predicted accurately using the proposed finite element analysis.